PENGARUH TINGKAT KESEHATAN BANK TERHADAP PERTUMBUHAN LABA - Nur Hidayati; Yeni Purwitosari (MAGISTER MANAJEMEN UNISMA, 2020)
The profit growth can be used as a measure of achievement of a bank in the assessment of bank performance. This can be achieved if the level of health of banks consisting Capital Adequacy Ratio, Assets Quality, Net Interest Margin, Return on Assets, Loan to Deposit Ratio and Interest Risk Ratio in accordance with the standards set by the government. For this study aims to assess how the influence of the bank to profit growth, particularly private banks non-foreign national 2013-2014 period amounting to 23 banks. By using hypothesis testing found that the Return On Asset and Loan to Deposit Ratio positive effect on the growth rate of bank profits, while the Capital Adequacy Ratio, kualiatas Assets, Net Profit Margin and Risk Ratio interst does not affect the bank's profit growth.Keywords: Health, Income Growth, Bank